A Detailed Evaluation on External Morphology of Raw Drug Samples of “Dasamoola”-Ten Roots in Ayurveda - S Raj, Asha; Oommen, Sara Monsy; V V, Shincymol (Pharmacognosy Reviews)
Ayurveda-The ancient science of life, is a traditional system of medicine originated and evolved in Indian sub-continent. It majorly utilises plant derivatives for the accomplishment of its main aim “Arogya” (health). The 21st century witnessed a huge advancement quality of life in humans due to the revolutionary upliftment in technology. But still 80% of world’s total population depends on herbal based medicines and therapies for primary health care. Owing to the high demand and rapid deforestation because of industrialisation, availability of authentic raw drugs for the herbal medicine industry is declining rapidly. “Dasamoola” is an important group of drugs in Ayurveda, in which root of ten drugs are collected and used together. Modern herbal industry utilises an array of physico-chemical techniques to ensure the authenticity, quality and purity of raw drugs. But still gross morphological examination plays a major role in drug identification. This study aims to collect and document authentic samples and to consolidate the important organoleptic features of “Dasamoola.” This study will provide insight to some unique identification features of each drug like faint aromatic odour of Agnimantha root, extremely porous and light weight of Patala root etc.
Keywords: Dasamoola; Ten roots; Ayurveda; Raw drug; Organoleptic features